Rheological processes in the slope massifs of the city of Kyiv - Максим Рева; Олександр Лисенко; Дмитро Чомко (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія)
Formulation of the problem. The paper examines landslide processes that occurred on the right bank of the city of Kyiv. The authors demonstrate the general statistics of the development of landslides in the city, which is a dangerous phenomenon for the safety of the city. In Kyiv, 42 landslides have been recorded, which are in the active phase. The authors identify the main reasons for the development of landslides as engineering-geological, geomorphological conditions, climate and anthropogenic impact. The article examines the use of GIS technologies as a modern and quite effective method of monitoring landslide processes. The authors focus attention on two landslides that occurred and differ from the rest due to the atypical mechanics of the process, which was affected by the overwetting of the soil mass. It was this difference that led to this scientific research. This theoretical study was conducted on a site in the Park of Vichnoyi Slavy, since by all indicators this slope has the potential for the development of just such a landslide. Overmoistened soil mass has a special mechanics of movement on the slope and is classified as – a landslide flows.